Attribute generalization mix-zone based on multiple secure computation - Bin WANG; Lei ZHANG; Guoyin ZHANG (Tongxin xuebao)
In order to cope with the problems of resist the attack of user tracking with attributes and resist the disguised attack in road networks,based on the conception of attribute generalization and the methods of homomorphic encryption,a privacy protection method to complete the calculation of attribute generalization in private state and achieve attribute generalization was proposed.The proposed method utilized the homomorphic encryption to achieve secret bidding selection with an agent,and then utilize secure multi-party computation to calculate the similar attributes and achieve the attribute generalization in the end.With the help of fully attribute generalization,this method can solve the problem of users can be tracked by the potential attributes,and at the same time the privacy calculation also does not reveal any information to participants,so this method can prevent the disguised attacker that obtains user’s information in mix-zone.At last,in order to demonstrate the superiority of the proposed method in both of academically and practicality,the security analysis and experimental verification are given,and the procedure of formulation verification and the result of experiment further substantiate the superiorities of the proposed method.